DESENVOLVIMENTO DE APARATO MODULAR PARA AQUISIÇÃO DE DADOS AMBIENTAIS GEORREFERENCIADOS - Soeira, Marcelo Rezende Calça; Pezzuto, Cláudia Cotrim (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The pursuit of sustainable urban development pathways demands better comprehension of the influences exerted by the urban fabric on local microclimates. Therefore, improvement of the tools and methods currently available for obtaining urban climatic data is of considerable importance. This study proposes a modular experimental instrument for georeferenced environmental data acquisition, geared towards the application of mobile measurement methodology. The prposed instrument's performance was compared to that of a reference equipment across three mobile measurement campaigns. While results show that the data collected by both instruments are in agreement, the acquisition capacity of the proposed instrument far exceeds that of the reference equipment in regards to measurement resolution, precision, frequency and storage, for a much lower cost. application was deemed suitable for urban climate research